Stable isotope dilution analysis of N-acetylaspartic acid in CSF, blood, urine and amniotic fluid: accurate postnatal diagnosis and the potential for prenatal diagnosis of Canavan disease - Jakobs, C; ten Brink, H.J; Langelaar, S.A; Zee, T; Stellaard, F; Macek, Milan; Sršňová, Klára; Sršeň, Štefan; Kleijer, W.J (Journal of inherited metabolic disease, 1991)
A sensitive and selective analytical technique is described for the determination of N-acetylaspartic acid in body fluids using stable isotope dilution in combination with positive chemical ionization mass spectrometry with selected ion monitoring. Control mean and ranges have been established: in urine 19.5 and 6.6-35.4 mumol/mmol creat.; in plasma 0.44 and 0.17-0.81 mumol/L; in cerebrospinal fluid 1.51 and 0.25-2.83 mumol/L; and in amniotic fluid 1.27 and 0.30-2.55 mumol/L. In a patient with Canavan disease, N-acetylaspartic acid concentration was elevated 80-fold in urine and 20-fold in plasma compared to the control means. A subsequent pregnancy of the mother was monitored and the N-acetylaspartic acid concentration in the amniotic fluid was within the control range and a healthy child was born.
Keywords: Infant; Aspartic Acid; těhotenství; plodová voda; amidohydrolasy; Humans; tělesné tekutiny; Body Fluids; referenční hodnoty; Amidohydrolases; prenatální diagnóza; ženské pohlaví; Indicator Dilution Techniques; Amniotic Fluid; kyselina asparagová; lidé; indikátorové diluční techniky; Pregnancy; Reference Values; Prenatal Diagnosis; kojenec; Female